2015
DOI: 10.1039/c5cp03671b
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed EPR dipolar spectroscopy at Q- and G-band on a trityl biradical

Abstract: Pulsed electron paramagnetic resonance (EPR) spectroscopy is a valuable technique for the precise determination of distances between paramagnetic spin labels that are covalently attached to macromolecules. Nitroxides have commonly been utilised as paramagnetic tags for biomolecules, but trityl radicals have recently been developed as alternative spin labels. Trityls exhibit longer electron spin relaxation times and higher stability than nitroxides under in vivo conditions. So far, trityl radicals have only bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 40 publications
2
40
0
1
Order By: Relevance
“…18 In the cited study the double-frequency oscillations were observed at ~ g ⊥ orientations of ED EPR spectrum, meaning that the ( x , y ) plane of each TAM is closely parallel to the spin-spin vector AB. In agreement with this conclusion, the opposite DEER orientation dependence in our case implies opposite TAM orientations relative to the spin-spin vector AB: the ( x , y ) plane of TAM is perpendicular to AB and to the DNA helix axis.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…18 In the cited study the double-frequency oscillations were observed at ~ g ⊥ orientations of ED EPR spectrum, meaning that the ( x , y ) plane of each TAM is closely parallel to the spin-spin vector AB. In agreement with this conclusion, the opposite DEER orientation dependence in our case implies opposite TAM orientations relative to the spin-spin vector AB: the ( x , y ) plane of TAM is perpendicular to AB and to the DNA helix axis.…”
mentioning
confidence: 81%
“…15 Resolution of the g -tensor components improves at higher frequencies; e.g., a recent PDS study at G-band (180 GHz) demonstrated orientation-selective Double Electron-Electron Resonance (DEER, also known as PELDOR 17 ) measurements on TAM spin labels. 18 Here, we use orientation selectivity to investigate the preferred TAM orientations in a set of doubly TAM-labeled 10-mer dsDNAs shown in Figure 1, in order to assess on this basis the underlying TAM-DNA interactions. In two dsDNAs, TAMs were attached using a relatively long piperazine linker ( I , II ), whereas in the third one ( III ), a much shorter amine linker was implemented for comparison of conformational flexibility.…”
mentioning
confidence: 99%
“…These new labels also show promise for single-frequency PDS measurements, where a long phase memory time and higher stability allow for room temperature distance measurements on immobilized biomolecules. 1721 …”
Section: Introductionmentioning
confidence: 99%
“…The distances between spin labels can be obtained using different approaches, including Pulsed Electron Double Resonance (PELDOR, also known as DEER) [31, 32], Double Quantum Coherence (DQC) EPR [33, 34], single-frequency technique for refocusing dipolar couplings (SIFTER) [35], Relaxation Enhancement (RE) [36,37]. Owing to the narrow linewidth, TAM is not suitable as a spin label for X-band DEER; however, if DQC or SIFTER is used, the narrow line of TAM becomes a huge advantage and leads to a higher sensitivity compared to nitroxides [27,28,38,39]. At high magnetic fields (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…G-band) the EPR linewidth of TAM increases due to the g-anisotropy and reaches ca. 130 MHz, thus allowing application of PELDOR/DEER as well [38]. …”
Section: Introductionmentioning
confidence: 99%